An enhanced target-enrichment bait set for Hexacorallia provides phylogenomic resolution of the staghorn corals (Acroporidae) and close relatives - Cowman, Peter F.; Quattrini, Andrea M.; Bridge, Tom C.L.; Watkins-Colwell, Gregory J.; Fadli, Nur; Grinblat, Mila; Roberts, T. Edward; McFadden, Catherine S.; Miller, David J.; Baird, Andrew H. (Molecular phylogenetics and evolution, 2020)
[Display omitted] •Genomic capture methods can resolve clades that lack decades of molecular marker development.•An enhanced bait setfor Hexacorallia recovers >2400 UCE/exon loci in stony corals.•Phylogenomics resolves coral relationships at deep and shallow time scales.•Well-supported clades in Acropora are not supported by macromorphological features. Targeted enrichment of genomic DNA can profoundly increase the phylogenetic resolution of clades and inform taxonomy. Here, we redesign a custom bait set previously developed for the cnidarian class Anthozoa to more efficiently target and capture ultraconserved elements (UCEs) and exonic loci within the subclass Hexacorallia. We test this enhanced bait set (targeting 2476 loci) on 99 specimens of scleractinian corals spanning both the “complex” (Acroporidae, Agariciidae) and “robust” (Fungiidae) clades. Focused sampling in the staghorn corals (genus Acropora) highlights the ability of sequence capture to inform the taxonomy of a clade previously deficient in molecular resolution. A mean of 1850 (±298) loci were captured per taxon (955 UCEs, 894 exons), and a 75% complete concatenated alignment of 96 samples included 1792 loci (991 UCE, 801 exons) and ~1.87 million base pairs. Maximum likelihood and Bayesian analyses recovered robust molecular relationships and revealed that species-level relationships within the Acropora are incongruent with traditional morphological groupings. Both UCE and exon datasets delineated six well-supported clades within Acropora. The enhanced bait set will facilitate investigations of the evolutionary history of many important groups of reef corals, particularly where previous molecular marker development has been unsuccessful.